Engineering properties and shear behaviour of high strength lightweight aggregate concrete incorporating oil-palm-boiler clinker / Lee Jin Chai - Lee , Jin Chai (2018)
Oil-palm-boiler clinker (OPBC) is waste by-products from palm oil mill. The research on incorporating OPBC as aggregate in normal weight concrete (NWC) to produce structural lightweight aggregate concrete has been studied in the past 20 years. The compressive strength of OPBC lightweight concrete in between 15 and 47 MPa with a density of 12 - 40% less than NWC has been achieved by previous researchers. This study presents the use of OPBC as coarse aggregate substitution of conventional coarse aggregate to produce a sustainable high strength lightweight aggregate concrete. From trial mixes, it was found that OBPC high strength lightweight concrete, with or without limestone powder, with 28-day compressive strength in the range of 50 to 60 MPa with an oven dry density of 1875-1997 kg/m3 can be produced. The OPBC concrete has very low sensitivity with regards to poor curing. However, it is recommended that this type of concrete be cured for a minimum period of 7 days. The 28-day splitting tensile strength of OPBC concrete was determined to be between 2.2 and 5.0 MPa, which surpassed the requirement for structural concrete. The 28-day flexural strength was measured in the range of 3.2 to 7.0 MPa. The ratio of flexural to compressive strength varied from 8.6 to 21.6% and fall in the range of high strength lightweight concrete. The modulus of elasticity was found to be between 16.8 and 38.0 GPa which is in the range of NWC of 14 to 41 GPa. With regards to durability, the initial water absorption of OPBC concrete is lower than 3% which is classified as good concrete by CEB-FIP. The lightweight expanded clay aggregate (LECA) concrete demonstrates a greater drying shrinkage than both the normal weight and OPBC concretes between 14 days and 90 days. From the age of 90 days to 220 days, there is no significantly increase. However, 220 days onwards, the LECA concrete exhibited the greatest increase in drying shrinkage rate. As compared to OPBC concrete without fly ash (FA), and ground granulated blast furnace slag (GGBFS) at the age of 28 days, the use of FA, GGBFS showed lower mechanical properties, water absorption and sorptivity. Increasing porosity and chloride permeability are 4.3 to 13% and 4 to 8%, respectively. However, resistance against chemical attack (acid and sulphate) and drying shrinkage are improved. For shear behaviour, OPBC reinforced concrete beam of grade 55 strength without shear reinforcement showed higher ultimate load carrying capacity compared to other lightweight concrete beams, however, about 8% lower than that of NWC reinforced concrete beam. The substitution of cement with FA in OPBC reinforced concrete beam has no significant effect on shear behaviour, although, by incorporating GGBFS, the shear behaviour was found like oil palm shell reinforced concrete beam. By high substitution of cement with FA and GGBFS in OPBC concrete helps to reduce CO2 emissions by around 50%. Therefore, the use of OPBC should be promoted to produce a cleaner and greener concrete that can benefit the construction and agricultural industries.